Prevalence of Deep Vein Thrombosis in Hospitalized Patients With Suspected Pulmonary Embolism Ruled Out by Multislice CT Angiography. (March 2018) - Vazquez, Fernando Javier; Posadas-Martinez, Maria Lourdes; Boietti, Bruno; Giunta, Diego; Gandara, Esteban
Current evidence suggests that for outpatients with suspected pulmonary embolism (PE), multislice computed tomographic angiography (CTPA) is sufficient to rule out PE. However, the accuracy of CTPA alone has not been established for hospitalized patients. Our goal was to determine the prevalence of deep vein thrombosis (DVT) in hospitalized patients who had PE ruled out by CTPA. We conducted a prospective cohort study of patients who developed symptoms indicative of PE, after being admitted to the hospital for any reason other than PE and were evaluated with multislice CTPA. The main outcome was proximal DVT. Between November 2011 and December 2014, 191 hospitalized patients were screened. A total of 99 patients satisfied our inclusion criteria. The average length of hospitalization for this group was 14 days (range: 2-127 days). While hospitalized, 54 (28%) patients underwent a major surgical procedure and 80 (79%) were receiving thromboprophylaxis. Of the 99 patients included, 7 (7.07%; 95% confidence intervals [CIs]: 3.4-13.8) were diagnosed with a proximal DVT. The likelihood of developing a proximal DVT was higher for those with subtle and nonspontaneously reported symptoms of DVT, odds ratio [OR] was 50.93 (95% CI: 5.35-2572) and for those classified as PE likely OR was 37.54 (95% CI: 4.05-186.1). Given the prevalence of DVT in hospitalized patients with suspected PE ruled out by a negative multislice CTPA, our study suggests that compression ultrasonography would, in fact, be justified for patients with these characteristics.